Evaluation And Application Of Molecular And Immunological Serotyping Techniques For Selected Avian And Human E. coli Strains - Sebate, Segomoco, Lesego, Ignatious. (Central University of Technology, Free State, 2019)
A link exists between human and animal diseases caused by E. coli. Avian pathogenic E. coli (APEC) causes detrimental economic losses in the poultry industry due to infections in poultry such as colibacillosis and cellulitis. In 2003, poultry producers were made aware that some avian diseases could be transmitted to humans, particularly via the faecal-oral route. For the identification of these E. coli strains, surface antigens are used. Based on surface antigens namely somatic (O), capsular (K) and flagella (H) antigens, different E. coli strains can be serotyped. The most common APEC strains are O1, O2 and O78, but serotypes O8, O15, O18, O36, O88, O109, O115 and O116 have also been reported as E. coli isolates associated with cellulitis and colibacillosis in poultry. E. coli strains O1:K1:H7, O18:K1:H7 and O15:K52:H1 have been linked to diseases in both mammals and birds. In South Africa, only enumeration is performed routinely to monitor the presence of E. coli in poultry processing plants, thus no serotyping occurs in this setting. For this reason, it is important to know which serotypes are prevalent, especially in poultry abattoirs, to prevent the possibility of such pathogens infecting humans via poultry. It was therefore the aim of this study to develop a method that can identify these pathogens at serotype level from environmental samples. To identify the three laboratory strains, both genotypic (molecular) and phenotypic (immunological) characteristics were considered. When using multiplex-PCR as a molecular serotyping technique, targeted genes (wzx-1, neuC, fliC, wzx-2 and fumC) were detected on the test strains. With the optimization of multiplex-PCR, it was possible to apply this technique to field isolates as well as to the environmental sample. One-step digestion of multiplex PCR allowed the differentiation of the O1:K1:H7, O18:K1:H7 and O15:K52:H1 APEC E. coli test strains. The method proved to be fairly simple and cost effective, yet such a method is currently not available in the poultry sector. Conversely, an array of immunological techniques was able to detect only flagellin antigens on both the O1:K1:H7 and O18:K1:H7 strains using plate agglutination on the test strains. Additionally, K1 bacteriophage was able to detect K1 antigens again on both O1:K1:H7 and O18:K1:H7 using zone of inhibition, pour plate and broth clearing assays. However, counter current immunoelectrophoresis results were inconclusive due to negative results on the targeted antigen (i.e., K52 antigen).